Determinants of the Coexistence Dual Form of Malnutrition in Pairs of Mother and Child Aged 6 – 59 Months in Bogor District 2019 - Krismanita, Maulina Dwi; Triyanti, Triyanti; Syafiq, Ahmad; Sudiarti, Trini (Kesmas, 2022)
The dual form of malnutrition (DFM) is defined as multiple nutritional problems in the same household and time. This study aimed to determine the related factor to DFM incidence in pairs of mothers and children aged 6–59 months in Bogor District in 2019. This cross-sectional study used secondary data on the Nutrition and Health of Babakan Madang Subdistrict Toddlers in 2019 and Nutrition Intake and Stunting of Children Under-Five in Bogor District, West Java Province, involving a total sample of 274 households. The dependent variable in this study was DFM, while the independent variables were maternal age during pregnancy, maternal height, maternal breastfeeding history, parity, family income, mother's and father's education level. Bivariate analysis involving the Chi-square test and multivariate analysis with multiple logistic regression tests was used in this study. The results revealed that DFM incidence in the Babakan Madang Subdistrict in 2019 was 42%. The determinants of DFM that were significantly related were maternal height (p-value = 0.000), maternal breastfeeding history (p-value = 0.027), and parity (p-value = 0.049). The analysis results showed that the dominant factor in the prevalence of DFM was the maternal height (OR = 2.704; 95% CI = 1.615-4.528). It is recommended to improving nutrition in adolescence, especially in the case of girls in their role as future mothers.